2017
DOI: 10.1021/acsami.6b16304
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Interface Issues in All-Solid-State Bulk-Type Lithium Ion Battery via an All-Composite Approach

Abstract: All-solid-state bulk-type lithium ion batteries (LIBs) are considered ultimate solutions to the safety issues associated with conventional LIBs using flammable liquid electrolyte. The development of bulk-type all-solid-state LIBs has been hindered by the low loading of active cathode materials, hence low specific surface capacity, and by the high interface resistance, which results in low rate and cyclic performance. In this contribution, we propose and demonstrate a synergistic all-composite approach to fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
102
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 33 publications
1
102
0
Order By: Relevance
“…[1,25,38] Also, many solid electrolyte materials are unstable at high voltages and may react with the materials of the electrodes. Some researchers have reported such composite electrolytes, including Li 0.33 La 0.557 TiO 3 -polyacrylonitrile (PAN), [44] Li 7 La 3 Zr 2 O 12 -PEO, [45][46][47] and Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 -PEO. [1,25] Composite electrolytes can potentially combine the advantages of both ceramics and polymers by providing a high ionic conductivity with a high cation transference number together with high flexibility and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…[1,25,38] Also, many solid electrolyte materials are unstable at high voltages and may react with the materials of the electrodes. Some researchers have reported such composite electrolytes, including Li 0.33 La 0.557 TiO 3 -polyacrylonitrile (PAN), [44] Li 7 La 3 Zr 2 O 12 -PEO, [45][46][47] and Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 -PEO. [1,25] Composite electrolytes can potentially combine the advantages of both ceramics and polymers by providing a high ionic conductivity with a high cation transference number together with high flexibility and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Among the many SSEs studied, [7][8][9][10][11][12][13][14] the cubic garnet phase SSEs [15][16][17][18][19][20][21] are more attractive because of their excellent chemical stability, [22,23] high ionic conductivities, [15,16,[24][25][26] and wide electrochemical potential window. [24,30,31] Direct contact between Li metal foil and garnet pellets normally results in poor contact and large interfacial resistance. [24,30,31] Direct contact between Li metal foil and garnet pellets normally results in poor contact and large interfacial resistance.…”
mentioning
confidence: 99%
“…Chen et al reported a PEO/LLZO CPE by tape casting method ( Figure a,b). The authors dispersed different contents of Al‐doped Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (Al‐LLZTO) powders into PEO/LiTFSI solutions ([EO]/[Li] = 12), and then casted electrolyte precursors onto the composite cathode.…”
Section: Structural Design Of Inorganic Fillers In Pcsesmentioning
confidence: 99%
“…b) Demonstration of the flexibility and safety tests of the all solid‐state LIBs. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Structural Design Of Inorganic Fillers In Pcsesmentioning
confidence: 99%